West African agriculture and climate change: A comprehensive analysis - Guinea - Condé, Sidafa; Jalloh, Abdulai; Nelson, Gerald C.; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
Guinea has a tropical climate with two alternating seasons, a November–March dry season and an April–October rainy season. In general, rainfall increases from north to south. Infant mortality has decreased, and life expectancy has increased. The improvement in these indicators may be attributed to improved health conditions, particularly vaccination of children, as well as the benefits of economic liberalization.